Avaliação do domínio ATPásico da proteína não estrutural 3 (NS3) do vírus da Zika e investigação de derivados de hidantoínas e oxadiazol como agentes antivirais baseados na estrutura da proteína - Osti, Ygor Gabriel Pontieri (Universidade Federal de São Carlos, 2022)
One of the great challenges in the field of public health in Brazil has been related to the existence of flaviviruses that cause diseases with high rates of contamination, such as to Dengue, Zika and Chikungunya. The challenge in combating them increases due to the conditions climatic conditions conducive to the dissemination of its vectors commonly classified within the genus Aedes, whose common vector among the three is Aedes aegypti. The presence of Zika virus in the national territory in 2015 and despite having been configured as epidemic, Zika had benign symptoms and low lethality, however, the factor of concern linked to the Zika virus (ZIKV) was the sudden emergence of complications Severe neurological disorders: Guillain-Barre syndrome in adults and Congenital ZIKV (microcephaly) in newborns, occurring at the time of the epidemic and lasting current days. There is still no cure or vaccine to prevent ZIKV infection, the main preventive measure, currently, the control of transmitting mosquitoes. In this way, the The search for molecules with the potential capacity to become drugs is extremely necessary and interesting. It is known that two processes are critical to the life cycle of the virus in the human host: (1) infection and (2) viral replication. The replication process depends essentially from the non-structural proteins encoded by the viral genome. The NS3 has two protein domains: serine protease (NS3Pro) and NTP-dependent RNA helicase (NS3Hel), responsible, respectively, for the cleavage of polyproteins after translation and for the unfolding of a double-stranded RNA prior to RNA polymerization and capping. Being thus, when processing fragment screening data, two fragments were observed promising agents acting as potential inhibitors of NS3Hel, being hydantoins and oxadiazole. However, the present work continued what the group has been doing, in the effort to search for drug candidate molecules against ZIKV and shows the screening of 28 molecules derived from hydantoins and oxadiazole tested against the ATPase activity of NS3Hel in order to explore promising molecules that inhibit this protein. Also carried out was Differential Scanning Fluorimetry (DSF) to assess thermal stability as well as binding affinity between promising protein-compounds. In these tests, six compounds showed promising inhibition profile above 70%, which will continue to be explored in future group trials.
Assessment of the ATPase domain of the Zika virus nonstructural protein 3 (NS3) and investigation of hydantoin and oxadiazole derivatives as antiviral agents based on in the structure of the protein
Keywords: ZIKV; NS3Hel; atividade ATPásica; hidantoínas; oxadiazol; CIENCIAS BIOLOGICAS::MICROBIOLOGIA::BIOLOGIA E FISIOLOGIA DOS MICROORGANISMOS::VIROLOGIA